2015
DOI: 10.1080/09537287.2015.1015060
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of S-DBR in four manufacturing SMEs: a research case study

Abstract: Production planning and control systems (PPCs) are tools that have a major effect on the performance of manufacturing companies. An inappropriate determination of the applicability of PPCs could seriously jeopardise the ability to achieve competitive priorities. This mistake can be expensive for any company, but proper implementation is particularly critical for small and medium enterprises (SMEs), which are characterised by limited access to financial resources. Simplified Drum-Buffer-Rope (S-DBR) is a PPC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…By the resulting outcomes, our proposed solution procedure successfully integrates the Sub-Tour reversal model and TOC. The results show the superiority of the TOC model in solving issues in logistics and answering the question mentioned by previous studies (see Schragenheim and Dettmer [24]; Lee et al [13]; Chang and Huang [14]; Benavides and Landeghem [25]; Chakravorty and Hales [26]). The TOC model achieves the logistics goal for increasing the return loading rate by increasing by more than 50%.…”
Section: The Simulation and Its Statisticssupporting
confidence: 83%
“…By the resulting outcomes, our proposed solution procedure successfully integrates the Sub-Tour reversal model and TOC. The results show the superiority of the TOC model in solving issues in logistics and answering the question mentioned by previous studies (see Schragenheim and Dettmer [24]; Lee et al [13]; Chang and Huang [14]; Benavides and Landeghem [25]; Chakravorty and Hales [26]). The TOC model achieves the logistics goal for increasing the return loading rate by increasing by more than 50%.…”
Section: The Simulation and Its Statisticssupporting
confidence: 83%
“…In research carried out on the Scopus and Web of Science databases, only nine papers published in journals involving the S-DBR method were identified. Of these, eight addressed applications in MTO environments (Lee et al, 2010;Souza & Baptista, 2010;Kim et al, 2010;Chang & Huang, 2011a, b, 2014Benavides & Van Landegheim, 2015;Chakravorty & Hales, 2016), while only one approached the MTA method (Souza & Pires, 2014). Lee et al (2010) address some difficulties that some production environments may impose when implementing the S-DBR in MTO environments.…”
Section: The S-dbr/mta System and Strategies To Improve Factory Resourcesmentioning
confidence: 99%
“…From a proposal for a production order sequencing method based on layer production buffer to monitor the status of the buffer (Chang & Huang (2011a, b), Chang & Huang (2014) proposed an enhanced simplified drum-buffer-rope (SDBR) model to be applied in a reentrant flow shop (RFS). More recently, applications of the S-DBR system have been studied, as in small and medium-sized companies, due to the simplified planning characteristics of such a system (Benavides & Van Landegheim, 2015), or in assessing the performance of work relationships (Chakravorty & Hales, 2016).…”
Section: The S-dbr/mta System and Strategies To Improve Factory Resourcesmentioning
confidence: 99%
“…Relying on Ikeziri et al (2019), a search for studies focused on the S-DBR method was carried out on the Scopus database. Among the studies found were those that showed production system improvements with S-DBR, which permitted greater flow (Buestán Benavides & Van Landeghem, 2015;Hales & Chakravorty, 2016) and reductions in response times (Hales & Chakravorty, 2016).…”
Section: Recent Studiesmentioning
confidence: 99%